VALIDATION METHOD OF ULTRAVIOLET SPECTROPHOTOMETRY DETERMINATION OF CONTENT IN AMBROXOL HCl TABLET - Tedy Kurniawan Bakri; Fathur Rahman Harun; Misrahanum .; Sadli . (Jurnal Natural, 2015)
Ambroxol Hydrochloride (Ambroxol HCI) is one of mucolytic drugs that is commonly used to dilute thesecretion within the respiratory tract. This process is completed by lowering the viscosity of mucopolysaccharides, in which its characteristic which is mucolytic within the respiratory tract. This research aims to conduct a validation of the UV spectrophotometry method in determining the level of ambroxol HCI in tablets. This methos is also used to obtain the level of amboxol HCI in tablets that are available in the market. The parameters of the validation are accuracy, precision, limit of detection (LOD), and limit of qualification (LOQ). The samples of ambroxol HCI was consisted of one (1)generic tablet and five (5) from branded tablets from the market. The results of the validation tested gave an accuracy of 99.58% in recovery percentage and Relative Standard Deviation (RSD) of 1.14%. These results showed that this method gave good precision and exactness, with the limit of detection (LOD) 0,1505 µg/ml andlimit of quantification (LOQ) 0,5018 µg/ml. These numbers are obtained from tablets with brands namely Lapimuc® (PT. Lapi) with its level of ambroxol HCI of 99,71 ± 0,64%; Epexol® (PT. Sanbe) with levels of ambroxol HCI of 99,78 ± 0,52%; Mucera® (PT. Otto) with levels of ambroxol HCI of 99,76 ± 0,5239%; Mucos® (PT. Meprofarm) with levels of ambroxol HCI of 99,8 ± 0,75%; Mucopect® (PT. Boehringer Ingelheim) with levels of ambroxol HCI of99,5 ± 0,70%; and finally a generic tablet with the of ambroxolHCl( PT. Phapros) of 99,6 ± 0,59%. All tablets used within this research have conform to the general levels of amboxol HCI in a tablet which is not less than 90.0% and not more that 110% from the number written in the regulation.